Implementation of formative assessment portfolio check with feedback to improve mastery of concept and habits of mind students on acid-base material. Issue 4 (February 2019) - Burhanudin, R; Nahadi, N; Firman, H
Abstract: This study aims to implement the formative assessment of checked portfolio with feedback to improve the mastery of concepts and habits of mind student on acid-base materials. The portfolio is a systematic collection of samples of learners' work resulting from the process of learning undertaken. Feedback is given in writing and verbally during the learning process takes a place. The method utilizes a quasi-experiment with pretest-posttest non-equivalent control group design. The instruments utilized to collect research datas are formative assessment of portfolio check formats with feedback, question of acid-base concept, questionnaire habits of mind, interview guides and student response questionnaires. The mastering test of acid-base concepts is validated by 5 chemist experts and forming CVR index (Content Validity Ratio) between 0, 60-1, 00. Reliability test of acid-base concept mastery was tested involving 60 respondents XI MIA 1 and MIA 2 class in Senior High School processed utilizable SPSS 24.0 argued coefficient alpha value of 0.76. Furthermore it will conduct a more experiment of formative portfolios with feedback that impacts on mastery of concepts and habits of mind.